Whispering Hypnosis: Phylogenetically Programmed Behavior and a Pluralistic Understanding of Hypnosis. Issue 3 (2nd January 2020) - Short, Dan
Abstract : Hypnosis is founded on a legacy of debate and zero-sum thinking as competing schools have argued for the value of one theoretical explanation at the expense of another. More recently, the discussion has turned to pluralistic modeling, with many researchers accepting four central constructs: imagination, suggestion, expectation, and trance experience. The aim of this paper is to introduce a fifth domain, instinct. Discoveries in comparative psychology, such as autoshaping and instinctual drift are used to highlight the importance of using suggestions that incorporate or are in service of phylogenetically programmed behavior. While it is not uncommon for hypnotic operators to intentionally trigger a single reflex for induction purposes, this paper shows the value of strategically incorporating constellations of reflexive behaviors and emotions that can be identified in terms of universal instincts found in humans and non-human animals; such as attachment, dominance-submission, catatonic immobility, competition, ownership, reciprocity, maternal instincts, and fraternal protectiveness. Highly complex interpersonal dynamics, which can occur during hypnosis, are simplified using the phylogenetic construct, as illustrated in clinical vignettes.